The Effect of Betel Leaf Extract on the Rigor Mortis Progress of Tilapia (Oreocromis niloticus) - Sapagustinah Sapagustinah (IHSA Institute, 2023)
The aim of this study was to determine the effect of various concentrations of betel leaf extract on the development of rigor mortis tilapia (Oreochromis niloticus). This research was conducted in June-August 2015 in the laboratory of the Faculty of Fisheries and Marine Sciences. Tilapia (Oreochromis niloticus) obtained from fish farmers in Tarakan. Tilapia (Oreochromis niloticus) is placed in an aquarium containing 100 liters of water. Samples were allowed to acclimate for 2 days before being used in the study. The body weight and length of the sample were measured. The concentration of betel leaf extract is 4%, 6%, 8% and 10%. The fish is sacrificed and put in a solution of betel leaf extract for one hour, then cooled. The thinning of the sample body length was measured and the percentage of thinning was calculated. Based on the results of this study, the best concentration of betel leaf extract is between 6% and 10%. Tilapia (Oreochromis niloticus) rigor Mortis was higher at a concentration of 6%. However, degradation is better at higher concentrations.